Alice in Wonderland Syndrome with Mononucleosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
Five children with "Alice in Wonderland" syndrome associated with infectious mononucleosis are reported from Assaf Harofeh Medical Center, Zerifin, and Sheba Medical Center, Tel Aviv University, Israel.